Pengaruh Pertumbuhan Perusahaan dan Jaminan terhadap Peringkat Obligasi - Fikriyah, Siti Hailatul; Wiyanti, Rahma (EAJ (Economic and Accounting Journal), 2024)
Bond rating is a prerequisite that must be taken before investors conduct bond investigations. This is because bond ratings provide informative statements about the probability of a company's debt default. In the bond rating process, rating agencies evaluate companies on many aspects, including financial and non-financial factors. The international rating agencies that provide bond ratings are S&P (Standard & Poor's) Corporation and Moody’s Investors. Meanwhile, the bond rating agency in Indonesia is PT Pefindo, and PT KASNIC or now better known as Moody’s Indonesia. Researchers rely more on the ratings issued by PT Pefindo because many companies listed on the Indonesia Stock Exchange (IDX) use Pefindo's services. Good bond ratings are reflected in a company's financial reports, where if the company's performance improves, its rating will rise, attracting investors to invest their capital. The purpose of this research is to determine the influence of company growth and collateral on bond ratings in construction sub-sector companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling method is done using purposive sampling. The data analysis technique in this study uses panel data regression analysis. The obtained sample consists of 48 data samples, resulting in the finding that both sales growth and collateral affect bond ratings. Keywords: Bond Rating, Company Growth, Collateral